2020
DOI: 10.3390/tropicalmed5030124
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Continued Participation in Tuberculosis Contact Investigation in a Low-Income, High-Burden Setting

Abstract: Setting: Outpatient clinics, Kota Kinabalu, Malaysia; January–April 2018. Objectives: To identify barriers to full participation in tuberculosis (TB) contact investigation. Methods: Cross-sectional study of knowledge, perceptions, and behaviours among TB contacts. This study was conducted among contacts who attended an initial clinic visit to explore retention in care. During this first visit, contacts were approached for participation in a questionnaire at a follow-up visit. Contacts who consented but did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Conventionally, it has been proven that sociodemographic factors such as age [ 4 ], gender [ 5 ], race [ 6 ], educational level [ 7 ], employment [ 8 ], health care worker [ 9 ], income [ 10 ], residency [ 11 ], nationality [ 12 ], country of origin [ 13 ], and smoking status [ 14 ] have a role in TB cases. However, evidence described in the literature confirmed the importance of conducting a study to better understand how air quality and weather can influence the cases of TB.…”
Section: Introductionmentioning
confidence: 99%
“…Conventionally, it has been proven that sociodemographic factors such as age [ 4 ], gender [ 5 ], race [ 6 ], educational level [ 7 ], employment [ 8 ], health care worker [ 9 ], income [ 10 ], residency [ 11 ], nationality [ 12 ], country of origin [ 13 ], and smoking status [ 14 ] have a role in TB cases. However, evidence described in the literature confirmed the importance of conducting a study to better understand how air quality and weather can influence the cases of TB.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative potential explanation for limited evidence of household clustering is that contact tracing at the household level may be effectively limiting household-based clusters. Qualitative work has demonstrated that contacts identified through school or workplace screening programmes in Kota Kinabalu are less likely to attend the clinic for screening than household contacts [ 36 ]. Together with the current data in which linked cases spread beyond households or sub-districts, this emphasizes the need for contact investigation to be better implemented in schools, workplaces and social networks.…”
Section: Discussionmentioning
confidence: 99%
“…[4][13] Various community-led organizations in TB case finding are effective and need to be implemented. [4][8][9] [14] Previous research has stated that partnerships with the community could improve access to health services in the prevention of tuberculosis. [15][16] This community involvement could improve TB case detection.…”
Section: The Role Of Tb Community In Detecting Tb Suspectsmentioning
confidence: 99%
“…[18] [9] Other challenges in finding suspects include a lack of training, the presence of stigma, a lack of public awareness about TB, and the inability to convince to carry out a sputum test. [9] [14] E3S Web of Conferences 317, 04018 (2021) ICENIS 2021 https://doi.org/10.1051/e3sconf /202131704018 For this reason, the role of community social workers in health can increase the national target for TB case detection by mobilizing the community in health services. [8] The TB community is a social worker is expected to help increase TB case detection; one of its activities is to conduct home visits to search for TB suspects.…”
Section: The Role Of Tb Community In Providing Counsellingmentioning
confidence: 99%
See 1 more Smart Citation